Peran Mediasi Transformasi Digital dalam Pengelolaan SDM terhadap Peningkatan Kinerja UMKM: Path Analysis - Landreas Utama, Lie; Sudarmiatin Sudarmiatin; Ludi Wishnu (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study aims to analyse the mediating role of digital transformation on the effect of human resource management (HRM) on MSME performance. The study used a quantitative approach and cross-sectional research design, data were collected from 74 MSME players through a closed questionnaire using a likert scale research instrument. The analysis technique used in this study used path analysis to determine the indirect effect of the mediating variable and examine the research data. The results showed that effective HR management has a significant effect on MSME performance. In addition, digital transformation is also proven to act as a mediator that strengthens the relationship between HR management and MSME performance. These findings provide insights for MSME players, especially members who are members of the Forbinus Nusantara community, to optimise HR management strategies and the application of digital technology to improve their performance in facing challenges in the digital era. This research is expected to provide practical recommendations for stakeholders in strengthening effectiveness in HR management in MSMEs.